Yugapravartaka Jayaśaṅkara Prasāda (Prakāśana Vibhāga Sūcanā aura Prasāraṇa Mantrālaya, 1966)
Collection of writings by noted Hindi authors on the personality and works of Jai Shankar Prasad, 1889-1937.